Application of voting methods to strategies analysis and assessment - Emma H. Danielyan (Изд-во НАН РА)
Classi¯cation of known voting methods in the frame of the Management Optimal Strategy Provision and Skill Assessment problems is given. Methods applicable to these problems are presented with pseudo code and their complexities are calculated. The applicability of voting methods is shown on the scheme with methods separation on two basic classes - Condorcet consistent and Scoring methods. The Kendall-Wei tournament participants ranking method is analyzed for mentioned problems.
Keywords: Mathematics